- Influence Mechanism of Serum Free Immunoglobulin Light Chain on Pulmonary Inflammatory Response and Serum Levels of Inflammatory Factors in Patients with Chronic Obstructive Pulmonary Disease: - - Yin, Cuiying (Journal of Medical Biochemistry, 2024)
Introduction: the pathogenesis of chronic obstructive pulmonary disease (COPD) is not fully understood. This work aimed to demonstrate the role of serum free light chains (sFLC) in the pulmonary inflammatory response of COPD patients and its relationship with serum inflammatory cytokine (IC) levels. Material and methods:eighty subjects were enrolled, including 40 COPD patients (COPD group) and 40 healthy controls (control group). All patients were further rolled into four subgroups regarding the Global Initiative for Chronic Obstructive Lung Disease (GOLD) staging criteria. The serum levels of sFLC and ICs were compared between the two groups, and their correlations with lung function indicators were analyzed. Results: the serum sFLC levels of COPD patients were markedly superior to those of healthy controls. The levels of serum sFLC and ICs (tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-8) gradually increased with the severity of the disease. The levels of ICs were negatively correlated with lung function indicators (FEV1% predicted, FEV1/FVC). Conclusion:these findings suggest that serum sFLC may play a critical role in pulmonary inflammatory response of COPD patients and serve as a potential indicator for evaluating COPD severity and predicting disease progression.
Keywords: Chronic obstructive pulmonary disease; Serum free immunoglobulin light chain; Inflammatory factors; Lung function index